Where the water meets the sky - Les Becquets, Diane (Simon & Schuster, 2026)
On a night in January, on the Garden Peninsula of Michigan, a farmhouse burns to the ground. A young child makes it out and flees into the woods with a book of matches in her hand. Ten years later, Abby, a lover of birds and the natural world, returns to Garden, to the woods and lakes and farms and fisheries of her childhood, to assist her uncle on an environmental study of trees. Her best friend, Brew, invites her to a party where she meets a troubled girl named Seda, on the run from her abusive ex. Abby sets out to protect Seda and introduces her to an abandoned cabin that becomes a sanctuary for them both. Here, Abby begins to process her unrequited feelings for Brew while also discovering the person she is becoming. She wants more for her life, a hunger both spiritual and physical, and seeks to understand the trauma of her childhood that took her mother from her. Abby cares deeply for the people and flora and fauna around her and identifies with the wounds of the environment. She is desperate to remember what happened the night of the fire and as the summer of 1996 unfolds, Abby will be forced to reckon with the truth.